2022
DOI: 10.1038/s41419-022-05190-0
|View full text |Cite
|
Sign up to set email alerts
|

Low quantity and quality of anti-spike humoral response is linked to CD4 T-cell apoptosis in COVID-19 patients

Abstract: In addition to an inflammatory reaction, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)-infected patients present lymphopenia, which we recently reported as being related to abnormal programmed cell death. As an efficient humoral response requires CD4 T-cell help, we hypothesized that the propensity of CD4 T cells to die may impact the quantity and quality of the humoral response in acutely infected individuals. In addition to specific immunoglobulins (Ig)A, IgM, and IgG against SARS-CoV-2 nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Having observed differences in the IgG response between vaccinated individuals and those previously infected with SARS-CoV-2, we then compared their IgA responses. We and others have shown that humoral response against the S protein also includes IgA ( 21 , 43 – 45 ). Furthermore, IgA were reported to dominate the early antibody response to SARS-CoV-2 ( 21 , 29 ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Having observed differences in the IgG response between vaccinated individuals and those previously infected with SARS-CoV-2, we then compared their IgA responses. We and others have shown that humoral response against the S protein also includes IgA ( 21 , 43 – 45 ). Furthermore, IgA were reported to dominate the early antibody response to SARS-CoV-2 ( 21 , 29 ).…”
Section: Resultsmentioning
confidence: 96%
“…We assessed in the S-Flow assay ( 21 ) the impact of such conformational changes using a mAb that recognizes the NTD domain. This mAb recognized cells expressing the Wuhan-Hu strain (fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In healthy immunocompetent adults, COVID-19 vaccinations induce humoral and cell-mediated responses (3, 4), of which neutralizing antibodies are associated with protective immunity (5). In addition, both CD4+ and CD8+ T cells are needed to generate a robust humoral response (6)(7)(8)(9) and antigen-specific T cells are shown to limit the disease severity (10). Previous studies on immunocompromised patients have demonstrated weak or absent antibody responses but robust cellmediated responses after two doses of the COVID-19 vaccine (11,12).…”
Section: Introductionmentioning
confidence: 99%